Pollination in species with dry stigmas the nature of the early stigmatic response and the pathway taken by pollen tubes - Elleman, C J (The New phytologist, 1992)
Interaction between the pollen grain, pollen tube and the stigma surface has been studied in five species regarded as possessing dry stigma surfaces; Brassica oleracea L., Arabidopsis thaliana (L.), Heynh, Papaver rhoeas L., Cosmos bipinnatus Cav. and Helianthus annuus L. In B. oleracea and A. thaliana, stigmatic response to pollination includes events in the papillar cytoplasm and changes to the stigmatic surface beneath the grain. In particular a specialized outer element of the cell wall expands prior to pollen tube penetration. The pollen tube, which enters through a 'foot' of pollen coating, grows in a space generated between an inner and the outer element of the wall and extends to the base of the papilla where it enters the middle lamellae of the subjacent cell layer. However, in A. thaliana tubes frequently were seen to penetrate all components of the stigmatic cell wall, an event only previously recorded in immature stigmas of B. oleracea. In self pollinations of self-incompatible B. oleracea involving strong S (incompatibility) alleles no changes take place in the papillar cell wall. In P. rhoeas the stigmatic surface responds to self and cross pollination by the secretion of electron-lucent material beneath the cuticle, causing it to become detached from the outer surface of the stigmatic cell wall. The pollen tubes then penetrate the cuticle and grow towards the base of the papilla in the space thus generated. The tubes continue to grow intercellularly in the transmitting tissue which lies horizontally in rays beneath the papillae. In members of the Compositae, C. bipinnatus and H. annuus, both stigma and pollen respond to pollination by producing copious quantities of an electron-opaque matrix, which frequently causes individual papillae to adhere together. Pollen tubes, which are formed following both compatible and incompatible intraspecific pollinations, grow into this matrix and toward the base of the papillae. There, in common with the other plants studied, they grow intercellularly and enter the transmitting tissue of the style. These findings are discussed in the light of current views of the mechanisms operating during angiosperm pollination and of the significance of the stigmatic response to the functioning of self-incompatibility mechanisms